A Study on the Prism Sheet Applied Double-Skin Facade for Saving Lighting Energy - JANG, Minwoo; BYUN, Younghoon; RYU, Ri; KIM, Yongseong (International Journal of Engineering and Technology, 2019)
With the recent increase in the use of lighting energy in the building sector and as skyscrapers are developed with glass envelopes, research on reducing lighting energy consumption by introducing natural light into the building is increasing. However, natural lighting systems have limited lighting energy reduction efficiency in buildings due to the application of operating technologies in order to reduce the lighting energy and improve the lighting performance. Therefore, the purpose of this study is to propose a double-skin facade for reducing lighting energy by using prism sheets, and to verify its effectiveness through the performance evaluation using a full-scale testbed. The conclusion is as follows. 1) This study derived the optimal variables for the double-skin without prism sheets (Case 1), double-skin with prism sheets on the outer skin of the cavity (Case 2), and the double-skin with prism sheets on the inner skin of the cavity (Case 3). 2) With the optimal variables, Case 3 was able to reduce lighting energy by 25.93% and 1.24%, respectively, compared to Case 1 and Case 2. By using the diffusion principle of the refraction of prisms sheets, the lighting energy reduction and the lighting performance were improved compared to the conventional double-skin. In addition, considering the reduction of lighting energy, the efficiency is considered to be higher than the conventional double skin. 3) Based on the optimal attachment angle of the prism sheet derived for each case, Case 3 was able to improve the uniformity by 68.94% and 2.26% in summer, and 55.0% and 6.90% in the mid-season, respectively, compared to Case 1 and Case 2. However, as the application of prism sheets reduces the uniformity in winter, it is preferable to remove the prism sheets during winter. This problem can be resolved by attaching and detaching the prism sheets or by using a double-skin window with blinds made of prism sheet material.Â